3,4-dihydroxybenzyl alcohol lithium direct regeneration of a spent lithium iron phosphate cathode
The use of lithium 3,4-dihydroxybenzyl alcohol generated by high-energy ball milling to regenerate and repair failed LFP cathode materials solves the problems of complex LFP cathode recycling methods and poor repair effects in existing technologies, achieving efficient and low-energy material regeneration and improving electrochemical performance.
Patent Information
- Application Number
- CN202411968389.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2026-06-30
AI Technical Summary
Existing LFP cathode recovery methods are complex to operate, highly polluting, and the recovered products are mostly alloys or metal salts. Furthermore, existing direct regeneration technologies are cumbersome, energy-intensive, and have poor remediation effects.
3,4-Dihydroxybenzyl alcohol lithium and lithium hydroxide were mixed by high-energy ball milling to generate 3,4-dihydroxybenzyl alcohol lithium, which was then used as a lithium replenishing agent and reducing agent to regenerate and repair failed LFP cathode materials. The activity of the material was restored by calcination to form lithium carbonate and alcohol hydroxyl reducing functional groups.
The regeneration of LFP cathode material was achieved at low temperature. The regenerated material exhibits excellent electrochemical activity, with a specific capacity of 162 mAh/g at 0.1C and a capacity retention of 89.5% after 50 cycles at 5C. It also improves the transport kinetics of lithium ions and electrons.
Smart Images

Figure CN122314786A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery materials technology, specifically to a method for directly regenerating failed lithium iron phosphate cathodes using lithium 3,4-dihydroxybenzyl alcohol. Background Technology
[0002] Lithium iron phosphate (LFP) batteries possess advantages such as high safety, long cycle life, low self-discharge rate, and environmental friendliness, playing a vital role in automotive, energy storage, and other fields. However, during the charging and discharging process, lithium ions continuously intercalate and deintercalate from the cathode material, inevitably causing lithium ion loss, known as lithium vacancy defects. These defects not only lead to Fe... 2+ Oxidized to Fe 3+ It will also induce some Fe 2+ The lithium ions migrate to the lithium site, forming Fe-Li antisite defects, blocking the diffusion pathway of Li ions, and ultimately leading to a decrease in the performance of LFP batteries until they become unusable. To fully utilize metal mineral resources and achieve sustainable development, developing recycling technologies for spent LFP batteries to ensure the full recycling and utilization of spent LFP cathode materials is of great significance.
[0003] In existing technologies, traditional LFP cathode recycling methods are complex to operate, highly polluting, and the recycled products are mostly alloys or metal salts, which can only be used as battery precursors. Emerging technologies for direct repair and regeneration of spent LFP cathodes, such as solid-state methods, hydrothermal methods, and electrochemical methods, have greater development prospects. However, existing direct LFP regeneration technologies still have technical problems such as cumbersome processes, the need for high-temperature treatment, high energy consumption, and poor material repair effects.
[0004] In view of this, it is necessary to develop a method for the direct regeneration of failed LFP cathodes using lithium 3,4-dihydroxybenzyl alcohol with a simple and efficient process and better repair effect. Summary of the Invention
[0005] In view of the technical problems existing in the background art, this application provides a method for directly regenerating failed LFP cathodes with lithium 3,4-dihydroxybenzyl alcohol. The method involves mixing 3,4-dihydroxybenzyl alcohol and lithium hydroxide by high-energy ball milling and reacting them, so that the lithium in the lithium hydroxide replaces the hydrogen on the hydroxyl group of 3,4-dihydroxybenzyl alcohol, to obtain lithium 3,4-dihydroxybenzyl alcohol. The lithium 3,4-dihydroxybenzyl alcohol is used as a lithium replenishing agent and reducing agent to directly regenerate and repair the failed LFP cathode material. The regenerated LFP cathode material has excellent electrochemical activity, with a specific capacity of 162 mAh / g at 0.1C and a capacity retention of 89.5% after 50 cycles at 5C.
[0006] This application provides a method for directly regenerating a failed lithium iron phosphate cathode using lithium 3,4-dihydroxybenzyl alcohol, comprising the following steps:
[0007] S1, the spent lithium iron phosphate cathode powder is mixed evenly with 3,4-dihydroxybenzyl alcohol and lithium hydroxide by high-energy ball milling, and then evaporated to dryness to obtain a mixture;
[0008] S2, calcine the mixture obtained in step S1 under a nitrogen atmosphere, and then cool it to room temperature to obtain the regenerated lithium iron phosphate cathode material.
[0009] Furthermore, in step S1, the lithium hydroxide reacts with a portion of the 3,4-dihydroxybenzyl alcohol during ball milling to generate lithium 3,4-dihydroxybenzyl alcohol and water.
[0010] Furthermore, the lithium 3,4-dihydroxybenzyl alcohol is obtained by replacing the hydrogen on the hydroxyl group of 3,4-dihydroxybenzyl alcohol with lithium in lithium hydroxide.
[0011] Furthermore, in step S1, the mass ratio of the failed lithium iron phosphate cathode powder to the lithium hydroxide is 1:(0.015-0.025).
[0012] Furthermore, in step S1, the mass ratio of the failed lithium iron phosphate cathode powder to the 3,4-dihydroxybenzyl alcohol is 1:(0.15-0.25).
[0013] Furthermore, in step S2, the calcination method is to heat the temperature to 650-750℃ and then hold it at that temperature for 3-5 hours.
[0014] Furthermore, in step S1, the high-energy ball milling method uses ethanol as the grinding agent.
[0015] Furthermore, in step S1, the solid-liquid ratio during the ball milling process is (40-60) g / L.
[0016] Furthermore, in step S2, the heating rate is 5℃ / min.
[0017] Furthermore, the calcination method involves heating the temperature to 700℃ and then holding it at that temperature for 4 hours.
[0018] The beneficial effects of this application are as follows:
[0019] This application provides a method for directly regenerating failed LFP cathodes using lithium 3,4-dihydroxybenzyl alcohol. The method involves mixing 3,4-dihydroxybenzyl alcohol and lithium hydroxide using a high-energy ball milling process and reacting them to allow lithium in the lithium hydroxide to replace the hydrogen on the hydroxyl group of 3,4-dihydroxybenzyl alcohol, thereby obtaining lithium 3,4-dihydroxybenzyl alcohol. This lithium 3,4-dihydroxybenzyl alcohol is then used as a lithium replenishing agent and reducing agent to directly regenerate and repair the failed LFP cathode material.
[0020] (1) This application utilizes the characteristic that lithium 3,4-dihydroxybenzyl alcohol can be pyrolyzed and carbonized at a relatively low temperature (650-750℃) to regenerate LFP cathode material in an environmentally friendly and energy-efficient manner. The regenerated LFP cathode material has excellent electrochemical activity, with a specific capacity of 162mAh / g at 0.1C and a capacity retention rate of 89.5% after 50 cycles at 5C.
[0021] (2) This application utilizes lithium carbonate obtained from the pyrolysis of lithium 3,4-dihydroxybenzyl alcohol and the reducing functional group of alcohol hydroxyl (-CH2OH) for lithium replenishment and reduction. Specifically, the reducing property of the alcohol hydroxyl group is used to restore the oxidized portion of the failed lithium iron phosphate cathode powder, while the lithium ions released from the lithium carbonate fill the lithium vacancies in the failed lithium iron phosphate cathode powder, replenishing the active lithium lost due to charge-discharge cycles. The pyrolysis of lithium 3,4-dihydroxybenzyl alcohol can also form an amorphous conductive carbon layer. This carbon layer covers the surface of the lithium iron phosphate sample, improving the lithium-ion and electron transport kinetics, and further enhancing the conductivity and cycle stability of the LFP cathode.
[0022] (3) This application utilizes the characteristic of the remaining unreacted 3,4-dihydroxybenzyl alcohol in the mixture obtained in step S1 to form a reducing atmosphere, and further reduces the iron ions in the failed lithium iron phosphate cathode powder to ferrous ions.
[0023] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, specific embodiments of this application are given below. Attached Figure Description
[0024] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0025] Figure 1 This is a scanning electron microscope (TEM) image of the regenerated lithium iron phosphate powder R-LFP-DHBALI-1 obtained in Example 1 of this application;
[0026] Figure 2 This is a TEM image of the regenerated lithium iron phosphate powder R-LFP-Li2CO3 obtained in Comparative Example 1 of this application. Detailed Implementation
[0027] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0029] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0030] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0031] To fully utilize metal mineral resources and achieve sustainable development, developing recycling technologies for spent LFP batteries is of great significance for ensuring the full recycling and utilization of spent LFP cathode materials. However, existing technologies, particularly traditional LFP cathode recycling methods, are complex, highly polluting, and the recovered products are mostly alloys or metal salts, which can only be used as battery precursors. Emerging direct repair and regeneration technologies for spent LFP cathodes, such as solid-state methods, hydrothermal methods, and electrochemical methods, show greater promise. Currently available direct LFP regeneration technologies still suffer from technical problems such as cumbersome processes, the need for high-temperature treatment, high energy consumption, and poor material repair effects.
[0032] To address the aforementioned technical problems, this application provides a method for directly regenerating failed lithium iron phosphate (LFP) cathodes using lithium 3,4-dihydroxybenzyl alcohol. This method involves mixing 3,4-dihydroxybenzyl alcohol and lithium hydroxide via high-energy ball milling and reacting them, allowing lithium from the lithium hydroxide to replace the hydrogen atom on the hydroxyl group of 3,4-dihydroxybenzyl alcohol, thus obtaining lithium 3,4-dihydroxybenzyl alcohol. This lithium 3,4-dihydroxybenzyl alcohol is then used as a lithium replenishing agent and reducing agent to directly regenerate and repair the failed LFP cathode material, resulting in a regenerated LFP cathode material with excellent electrochemical activity.
[0033] This application provides a method for directly regenerating a failed lithium iron phosphate cathode using lithium 3,4-dihydroxybenzyl alcohol, comprising the following steps:
[0034] S1, the spent lithium iron phosphate cathode powder is mixed evenly with 3,4-dihydroxybenzyl alcohol and lithium hydroxide by high-energy ball milling, and then evaporated to dryness to obtain a mixture.
[0035] In some embodiments, the high-energy ball milling method uses ethanol as the grinding agent, and the solid-liquid ratio during the ball milling process is (40-60) g / L.
[0036] In some embodiments, the mass ratio of depleted lithium iron phosphate cathode powder to 3,4-dihydroxybenzyl alcohol is 1:(0.15-0.25), and the mass ratio of depleted lithium iron phosphate cathode powder to lithium hydroxide is 1:(0.015-0.025).
[0037] During ball milling, a portion of lithium hydroxide reacts with a portion of 3,4-dihydroxybenzyl alcohol to produce lithium 3,4-dihydroxybenzyl alcohol and water. The lithium 3,4-dihydroxybenzyl alcohol is obtained by substituting a hydrogen atom from the hydroxyl group of 3,4-dihydroxybenzyl alcohol with lithium hydroxide. The structural formula of lithium 3,4-dihydroxybenzyl alcohol is as follows:
[0038]
[0039] S2, calcine the mixture obtained in step S1 under a nitrogen atmosphere, and then cool it to room temperature to obtain the regenerated lithium iron phosphate cathode material.
[0040] In some embodiments, the heating rate is 5°C / min.
[0041] In some embodiments, the calcination method is to heat the temperature to 650-750°C and then hold it at that temperature for 3-5 hours, preferably to heat the temperature to 700°C and then hold it at that temperature for 4 hours.
[0042] The calcination temperature needs to be controlled within a limited range (650-750℃) to ensure the effective decomposition of lithium 3,4-dihydroxybenzyl alcohol and the uniform diffusion of lithium ions. Excessive temperature may cause material sintering, while insufficient temperature may lead to incomplete reaction and affect the regeneration effect.
[0043] The reaction time also needs to be controlled within a limited range (3-5h) to ensure that lithium 3,4-dihydroxybenzyl alcohol reacts fully with the LFP cathode material. Too long a reaction time may cause the material to be over-sintered, reducing its activity; too short a reaction time may cause incomplete reaction, which will also affect the regeneration effect.
[0044] During calcination, lithium 3,4-dihydroxybenzyl alcohol in the mixture decomposes to yield lithium carbonate and reducing functional groups (-CH2OH). The reducing properties of the hydroxyl groups can restore the oxidized portions of the spent lithium iron phosphate cathode powder. Simultaneously, the lithium ions released from lithium carbonate fill lithium vacancies in the spent lithium iron phosphate cathode powder, replenishing the active lithium lost due to charge-discharge cycles. The remaining 3,4-dihydroxybenzyl alcohol in the mixture undergoes direct pyrolysis, creating a reducing atmosphere. This atmosphere, along with the hydroxyl groups, participates in the reduction reaction, reducing the iron ions in the spent lithium iron phosphate cathode powder to ferrous ions.
[0045] In addition, the pyrolysis of lithium 3,4-dihydroxybenzyl alcohol can also form an amorphous conductive carbon layer, which covers the surface of lithium iron phosphate samples and improves the transport kinetics of lithium ions and electrons.
[0046] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0047] Example 1
[0048] Example 1 provides a method for directly regenerating failed lithium iron phosphate cathodes using lithium 3,4-dihydroxybenzyl alcohol, comprising the following steps:
[0049] S1. 10g of depleted lithium iron phosphate cathode (S-LFP) powder, 2g of 3,4-dihydroxybenzyl alcohol, 0.18g of lithium hydroxide, and 240mL of ethanol were mixed evenly by high-energy ball milling at 500rpm. The solvent was then evaporated to obtain the mixture.
[0050] S2, the mixture obtained in step S1 is placed in a heat treatment furnace and heated to 700°C at a rate of 5°C / min under a nitrogen atmosphere, held for 4 hours, and then cooled to room temperature to obtain the regenerated lithium iron phosphate cathode material, denoted as R-LFP-DHBALI-1.
[0051] Example 2
[0052] Example 2 provides a method for directly regenerating failed lithium iron phosphate cathodes using lithium 3,4-dihydroxybenzyl alcohol, comprising the following steps:
[0053] S1. 12g of depleted lithium iron phosphate cathode powder, 2g of 3,4-dihydroxybenzyl alcohol, 0.18g of lithium hydroxide, and 280mL of ethanol were mixed evenly by high-energy ball milling at 500rpm. The solvent was then evaporated to obtain a mixture.
[0054] S2, the mixture obtained in step S1 is placed in a heat treatment furnace and heated to 650°C at a rate of 5°C / min under a nitrogen atmosphere, held for 5 hours, and then cooled to room temperature to obtain the regenerated lithium iron phosphate cathode material, denoted as R-LFP-DHBALI-2.
[0055] Example 3
[0056] Example 3 provides a method for directly regenerating a failed lithium iron phosphate cathode using lithium 3,4-dihydroxybenzyl alcohol, comprising the following steps:
[0057] S1, 8g of depleted lithium iron phosphate cathode powder, 2g of 3,4-dihydroxybenzyl alcohol, 0.18g of lithium hydroxide, and 200mL of ethanol were mixed evenly by high-energy ball milling at 500rpm, and the solvent was evaporated to obtain a mixture.
[0058] S2, the mixture obtained in step S1 is placed in a heat treatment furnace and heated to 750°C at a rate of 5°C / min under a nitrogen atmosphere, held for 3 hours, and then cooled to room temperature to obtain the regenerated lithium iron phosphate cathode material, denoted as R-LFP-DHBALI-3.
[0059] Comparative Example 1
[0060] The difference between Comparative Example 1 and Example 1 is that lithium carbonate is used as the lithium replenishing agent. Specifically, in step S1, 10g of depleted lithium iron phosphate cathode (S-LFP) powder, 0.28g of lithium carbonate, and 200mL of ethanol are mixed evenly by high-energy ball milling at 500rpm, and the solvent is evaporated to obtain a mixture. The rest is roughly the same as in Example 1, and will not be repeated here.
[0061] The surface morphology of the regenerated lithium iron phosphate powder R-LFP-DHBALI-1 obtained in Example 1 and the regenerated lithium iron phosphate powder R-LFP-Li2CO3 obtained in Comparative Example 1 were tested using transmission electron microscopy (TEM). Please refer to [link to TEM]. Figures 1 to 2 As shown, Figure 1 The TEM image of R-LFP-DHBALI-1 shows that a uniform carbon coating has formed on the sample surface, which consists of carbonaceous residues produced by the decomposition of lithium 3,4-dihydroxybenzyl alcohol. Figure 2 The TEM image of R-LFP-Li2CO3 shows that there is almost no carbon layer on the sample surface.
[0062] Elemental analysis was performed on the failed lithium iron phosphate cathode material S-LFP, the regenerated lithium iron phosphate powder R-LFP-DHBALI-1 obtained in Example 1, and the regenerated lithium iron phosphate powder R-LFP-Li2CO3 obtained in Comparative Example 1 using inductively coupled plasma atomic emission spectrometry (ICP-AES). The test results are shown in the table below.
[0063] project ICP (Li:P) S-LFP 0.91 R-LFP-DHBALI-1 1.0 <![CDATA[R-LFP-Li2CO3]]> 1.01
[0064] As can be seen, in the lithium iron phosphate powder repaired with lithium 3,4-dihydroxybenzyl alcohol or lithium carbonate, the ratio of Li to P both reached 1, indicating that lithium has been successfully replenished.
[0065] A half-lithium battery was prepared by using lithium foil as the counter electrode and polypropylene (PP) film as the separator, and dissolving 1M LiPF6 in ethylene carbonate / dimethyl carbonate (EC / DMC, volume ratio 1:1) as the electrolyte. Then, the battery was assembled with spent lithium iron phosphate powder (S-LFP) and regenerated lithium iron phosphate powder (R-LFP-DHBALI-1) obtained in Example 1 as positive electrodes. The specific capacity and rate performance of the battery were then tested, and the test results are shown in the table below.
[0066]
[0067] As can be seen, compared with S-LFP and R-LFP-Li2CO3, the specific capacity of the cathode material R-LFP-DHBALI-1, regenerated from lithium 3,4-dihydroxybenzyl alcohol, is significantly improved, reaching 161 mAh / g at 0.1C, which is 6 mAh / g higher than that of R-LFP-Li2CO3, essentially reaching the level of new materials. Furthermore, the cycle stability of R-LFP-DHBALI-1 is also significantly enhanced; after multiple charge-discharge cycles, the capacity decay rate is still 89.5%, which is 10.2% higher than that of R-LFP-Li2CO3.
[0068] In summary, the regenerated lithium iron phosphate cathode material obtained by lithium 3,4-dihydroxybenzyl alcohol remediation in this application has a uniform carbon coating on its surface, which greatly increases the conductivity of the product. Simultaneously, this material exhibits excellent electrochemical activity; lithium batteries prepared using it achieve a specific capacity of 161 mAh / g at 0.1C and retain 89.5% of their capacity after 50 cycles at 5C.
[0069] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A method for direct regeneration of a 3,4-dihydroxybenzyl alcohol lithium-depleted lithium iron phosphate cathode, characterized in that, Includes the following steps: S1, the spent lithium iron phosphate cathode powder is mixed evenly with 3,4-dihydroxybenzyl alcohol and lithium hydroxide by high-energy ball milling, and then evaporated to dryness to obtain a mixture; S2, calcine the mixture obtained in step S1 under a nitrogen atmosphere, and then cool it to room temperature to obtain the regenerated lithium iron phosphate cathode material.
2. The method of directly regenerating a spent lithium iron phosphate cathode of 3,4-dihydroxybenzyl alcohol according to claim 1, characterized in that, In step S1, the lithium hydroxide reacts with a portion of the 3,4-dihydroxybenzyl alcohol during ball milling to generate lithium 3,4-dihydroxybenzyl alcohol and water.
3. The method of directly regenerating a spent lithium iron phosphate cathode of 3,4-dihydroxybenzyl alcohol lithium according to claim 2, characterized in that, The lithium 3,4-dihydroxybenzyl alcohol is obtained by replacing the hydrogen on the hydroxyl group of 3,4-dihydroxybenzyl alcohol with lithium in lithium hydroxide.
4. The method of directly regenerating a spent lithium iron phosphate cathode of 3,4-dihydroxybenzyl alcohol according to claim 1, characterized in that, In step S1, the mass ratio of the failed lithium iron phosphate cathode powder to the lithium hydroxide is 1:(0.015-0.025).
5. The method of directly regenerating a spent lithium iron phosphate cathode of 3,4-dihydroxybenzyl alcohol lithium according to claim 1, characterized in that, In step S1, the mass ratio of the failed lithium iron phosphate cathode powder to the 3,4-dihydroxybenzyl alcohol is 1:(0.15-0.25).
6. The method of directly regenerating a spent lithium iron phosphate cathode of 3,4-dihydroxybenzyl alcohol according to claim 1, wherein, In step S2, the calcination method is to heat the temperature to 650-750℃ and then hold it at that temperature for 3-5 hours.
7. The method for directly regenerating failed lithium iron phosphate cathodes using lithium 3,4-dihydroxybenzyl alcohol according to claim 1, characterized in that, In step S1, the high-energy ball milling method uses ethanol as the grinding agent.
8. The method of directly regenerating a spent lithium iron phosphate cathode of 3,4-dihydroxybenzyl alcohol lithium according to claim 1, characterized in that, In step S1, the solid-liquid ratio during the ball milling process is (40-60) g / L.
9. The method of directly regenerating a spent lithium iron phosphate cathode of 3,4-dihydroxybenzyl alcohol lithium according to claim 1, characterized in that, In step S2, the heating rate is 5℃ / min.
10. The method of directly regenerating a spent lithium iron phosphate cathode of claim 6, wherein, Furthermore, the calcination method involves heating the temperature to 700℃ and then holding it at that temperature for 4 hours.